Effect of innovation on company performance with environmental performance as a mediating variable - Zaenal Fanani, Iman Harymawan, Elsa Nadia Tari, (Opción, 2020)
The ASEAN Economic Community (AEC), which enacted in early 2016, has caused business competition in Indonesia even tighter. This encourages the company to form an ability to innovate in order to achieve unique and superior resources so that competitive superiority can be achieved. This study aims to analyze the effect of innovation on company performance with environmental performance as a mediating variable in manufacturing sector companies listed on the Indonesia Stock Exchange of 2011-2015. Results showed that innovation has a negative effect but not significant on company performance. Inversely related to the findings, innovation has a positive effect on the company’s environmental performance. Environmental performance also has a positive effect on company performance.